Psycho - Perkins, Anthony 1932-1992; Miles, Vera 1929-; Gavin, John 1931-2018; Leigh, Janet 1927-2004 (Universal Studios, 2003)
Horror melodrama in which a woman disappears after spending the night in an isolated motel which adjoins an eerie Victorian mansion, inhabited by a disturbed young man and his mother.
Orig.: USA 1960. - Starring [u.a.]: Anthony Perkins, Norman Bates. Janet Leigh, Marion Crane. Vera Miles, Marions Schwester.
Keywords: Bates, Norman (Fictitious character) -- Drama; Feature films -- Video recordings; Horror films -- Video recordings; Hotelkeepers -- Drama; Murderers -- Drama; Suspense in motion pictures, television, etc.; Horrorfilm; DVD-Video